'The house cannot stay empty': a case of young rural Nepalis negotiating multilocal householding. Issue 2 (4th May 2017) - Korzenevica, Marina; Agergaard, Jytte
ABSTRACT: Over the past few decades, the mobility of young people abroad for education and labour has been rapidly increasing in Nepal, which has impacted both rural communities and household life. Based on ethnographic field data from Eastern Nepal, this paper explores how multilocality affects the socio-spatial dimensions of householding, i.e. how siblings negotiate their roles as movers and stayers in relation to household obligations, individual aspirations and shifting socio-economic opportunities. This paper draws on and contributes to scholarly debates on how migration impacts social transformation in places, with a particular focus on the dynamics of multilocal householding. We argue that a common agreement between generations and siblings that 'the house cannot stay empty' reinforces the importance of the household as a meaningful place exercised through the maintenance of traditional intra- and intergenerational contracts and the practice of rotating presence and absence.